Pertanggungjawaban Pelaku Usaha Apabila Konsumen Mengalami Kerugian Jual Beli Di Internet Menurut Undang-Undang Informasi Transaksi Elektronik - Mardiyati, Siti (Lex Librum : Jurnal Ilmu Hukum, 2023)
Abstract Buying and selling via the internet (e-commerce) all the formalities usually used in conventional transactions are reduced, where consumers can collect and compare information such as goods and services more freely without being limited by territorial boundaries (borderless), e-commerce not only provides convenience for consumers, but this development makes it easier for producers to market products that affect cost and time savings. Legal certainty for electronic transactions on the Internet in Law Number 19 of 2016 concerning Electronic Information and Transactions and legal action for one of the parties, namely consumers, when they are harmed in electronic transactions on the Internet, the results obtained are that business actors when offering business products via the internet must provide correct information. so that legal certainty to consumers in the future if there is a dispute over goods that do not come or are lost. Keywords: Accountability, Consumers, Buying and selling, Internet.